Pengurangan Downtime Mesin Offset di PT X - Jennifer Claudia; Felecia Felecia (Jurnal Titra, 2017)
X, Ltd is a company engaged in the field of packaging printing. The company has a main engine in the form of offset machines used to print the packaging so it needs a continuous process in order to meet customer demand. Offset machines experience downtime of 51% based on past data of companies that want to be reduced. The cause of machine downtime is setup during changeover and preventive maintenance process. Research was conducted to reduce downtime of offset machine by DMAIC method. How to reduce changeover time by using Single Minute Exchange Dies (SMED) tools. The data were collected on both workgroups and proposed improvements based on cause and effect diagrams on human factors, machines and methods, and scheduling setup. Suggested scheduling schedules with internal and external activity sharing, where internal activity is performed when the machine stops and externally is performed while the machine is running. Improvements made to reduce machine downtime with an average of 25.39%.